Catalytic Performance of TiO2–Carbon Mesoporous-Derived from Fish Bones in Styrene Oxidation with Aqueous Hydrogen Peroxide as an Oxidant - Mukhamad Nurhadi; Ratna Kusumawardani; Teguh Wirawan; Sumari Sumari; Sin Yuan Lai; Hadi Nur (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
The catalytic performance of titania-supported carbon mesoporous-derived from fish bones (TiO2/CFB) has been investigated in styrene oxidation with aqueous H2O2. The preparation steps of (TiO2/CFB) catalyst involved the carbonization of fish bones powder at 500 °C for 2 h. followed by impregnation of titania using titanium(IV) isopropoxide (500 µmol) precursor, and calcined at 350 °C for 3 h. The physical properties of the adsorbents were characterized using Fourier transform infrared, X-ray diffraction (XRD), Scanning electron microscopy with energy dispersive X-ray (SEM-EDX), and nitrogen adsorption-desorption studies. The catalytic test was carried out using styrene oxidation with H2O2 as an oxidant at room temperature for 24 h. Its catalytic activity was compared with Fe2O3/CFB, CuO/CFB, TiO2, and CFB catalysts. It is demonstrated that the catalytic activity of TiO2/CFB catalyst has the highest compared to Fe2O3/CFB, CuO/CFB, TiO2, and CFB catalysts in the oxidation of styrene with styrene conversion ~23% and benzaldehyde selectivity ~90%. Kinetics of TiO2/CFB catalyzed oxidation of styrene has been investigated and mechanism for oxidation of styrene has been proposed. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA   License (https://creativecommons.org/licenses/by-sa/4.0).